Efficient communication protocol of group negotiation in VANET - Mu HAN; Lei HUA; Liangmin WANG; Haobin JIANG; Shidian MA (Tongxin xuebao)
An efficient communication protocol of group negotiation was proposed.The protocol adopted self-checking authentication in group to avoid the nodes sending certificates to the authentication center which improved the efficiency of identification.At the same time,the group establishment among nodes which through negotiation ensured the communication confidentiality and prevented the phenomenon of single-point failure.Besides,a group key transmission scheme was proposed to reduce the frequency of authentication for legal vehicles and improve the speed of joining in the group.At the end,theoretical analysis and simulation results demonstrate that the proposed protocol not only meets the security requirements of communication in VANET,but also shows much better performance than previous reported schemes on verification delay,transmission overhead and average delay.